Diverse state‐level marine aquaculture policy in the United States: Opportunities and barriers for industry development. (13th November 2021) - Lester, Sarah E.; Gentry, Rebecca R.; Lemoine, Hayley R.; Froehlich, Halley E.; Gardner, Luke D.; Rennick, Mae; Ruff, Elizabeth O.; Thompson, Kimberly D.
Abstract: Marine aquaculture (mariculture) plays a relatively small role in the United States' domestic seafood production, despite considerable scope for industry development and high volumes of imported farmed seafood resulting in a significant trade deficit. Currently, most mariculture in the United States occurs in nearshore waters or land‐based tanks and is regulated and guided using state‐level policy, with a relative absence of national coordinating mechanisms to link the patchwork of state policies. There is no comprehensive evaluation showing how different state policies may be enabling or impeding mariculture development. In response, we provide the first systematic overview of state‐level mariculture policy for the 23 coastal marine states in the United States. We compiled information for 16 aquaculture and mariculture policy attributes, including legislation, regulations and management characteristics, particularly those that could enable mariculture development. We found considerable heterogeneity in how states govern and regulate mariculture. As examples, 48% of states have an aquaculture development act, 35% have spatial zoning specifically for mariculture and only 26% have a government‐provided mariculture best management practices document. We examined the relationship between enabling policies and metrics of mariculture output (e.g. production value, number of farms), and while the effect of enabling policy is often equivocal, certain features stand out as important (e.g. government‐provided best management practices). Overall, this policy synthesis suggests approaches that may be influential in enabling mariculture development, which could inform new state‐level policies, an effective overarching federal policy in the United States, or policies in other countries seeking to support an expanded mariculture industry.